Anti-corruption Action: A Project-Based Anti-corruption Education Model During COVID-19 - Sumaryati,; Suyadi,; Nuryana, Zalik; Asmorojati, Anom Wahyu (Frontiers in Education, 2022)
Education can be used as a preventive measure to decrease corruption cases during the COVID-19 pandemic. However, anti-corruption education is not enough with cognitive knowledge since more emphasis should be laid on affective and psychomotor actions. A project-based learning model was used to package these actions based on factual learning resources. Therefore, this study aims to develop a project-based learning model in online anti-corruption during the pandemic. Pendidikan Pancasila dan Kewarganegaraan (PPKn) is the Pancasila and Citizenship Education in Universitas Ahmad Dahlan, Indonesia was used as research setting. Furthermore, this participatory thematic study uses 28 PPKn students for the anti-corruption education course in the odd semester 2020/2021. Google forms, online focus group discussions, and documentation (task reports) methods were adopted for data collection, and the analysis was conducted through reduction, classification, and interpretation. The results showed the development of fourteen anti-corruption actions in online media, and each one has a different target group according to its content. Therefore, anti-corruption learning does not stop at the realm of cognition but also affection which has an impact on the transformation of social media. The actions to prevent corruption are still needed even though the pandemic is over considering the new confirmed cases.